Afiksasi Pembentuk Verba Transitif Dalam Novel Fatamorgana Di Segitiga Emas Karya Suryatini N Ganie - Luci Komala Bintang; Siti Ainim Liusti (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
This study aims to describe the affixes that form transitive verbs in the novel Fatamorgana in the Golden Triangle by Suryatini N Ganie, which includes the types of affixes that form verbs, patterns of verb formation, and the meaning of the affixes that form transitive verbs in the novel Fatamorgana in the Golden Triangle by Suryatini N Ganie. This type of research is descriptive qualitative research. The research data is in the form of words that experience affixation in the novel Fatamorgana in the Golden Triangle by Suryatini N Ganie. Methods of data collection using note takers. The technique of analyzing the data is classifying the affixation data forming transitive verbs, identifying the data, and concluding the data. Data validation technique is trigulation technique. The results of the study concluded that in the process of affixation forming transitive verbs in the novel Fatamorgana in the Golden Triangle by Suryatini N Ganie, it consists of 105 data of me- prefixes, 6 data of me-,-i affix combinations and 54 data of me-,-an affix combinations. There is a change in word class from nouns to verbs, adverbs to verbs, adjectives to verbs, and pronouns to verbs. The patterns of verb formation are (me- + D (Adj/ V/ N/ Pron/ Adv), (me- + D (V) + -i) and (memper- + D (N/ Adj/ V) + -kan). The affixation process results in grammatical changes.